Comparison of test-negative and syndrome-negative controls in SARS-CoV-2 vaccine effectiveness evaluations for preventing COVID-19 hospitalizations in the United States. Issue 48 (15th November 2022) - Turbyfill, Caitlin; Adams, Katherine; Tenforde, Mark W.; Murray, Nancy L.; Gaglani, Manjusha; Ginde, Adit A.; McNeal, Tresa; Ghamande, Shekhar; Douin, David J.; Keipp Talbot, H.; Casey, Jonathan D.; Mohr, Nicholas M.; et al.
Highlights: The test-negative design has been widely used for evaluating COVID-19 vaccine effectiveness, yet there is an absence of evidence on comparability with traditional case-control designs. Despite demographic and clinical differences, the use of test-negative and hospital-based syndrome-negative controls yields similar COVID-19 vaccine effectiveness results. The test-negative design is a valid approach to estimating vaccine effectiveness against COVID-19 hospitalization. Abstract: Background: Test-negative design (TND) studies have produced validated estimates of vaccine effectiveness (VE) for influenza vaccine studies. However, syndrome-negative controls have been proposed for differentiating bias and true estimates in VE evaluations for COVID-19. To understand the use of alternative control groups, we compared characteristics and VE estimates of syndrome-negative and test-negative VE controls. Methods: Adults hospitalized at 21 medical centers in 18 states March 11–August 31, 2021 were eligible for analysis. Case patients had symptomatic acute respiratory infection (ARI) and tested positive for SARS-CoV-2. Control groups were test-negative patients with ARI but negative SARS-CoV-2 testing, and syndrome-negative controls were without ARI and negative SARS-CoV-2 testing. Chi square and Wilcoxon rank sum tests were used to detect differences in baseline characteristics. VE against COVID-19 hospitalization was calculated using logistic regression comparing adjusted odds of prior mRNA vaccination between cases hospitalized with COVID-19 and each control group. Results: 5811 adults (2726 cases, 1696 test-negative controls, and 1389 syndrome-negative controls) were included. Control groups differed across characteristics including age, race/ethnicity, employment, previous hospitalizations, medical conditions, and immunosuppression. However, control-group-specific VE estimates were very similar. Among immunocompetent patients aged 18–64 years, VE was 93 % (95 % CI: 90–94) using syndrome-negative controls and 91 % (95 % CI: 88–93) using test-negative controls. Conclusions: Despite demographic and clinical differences between control groups, the use of either control group produced similar VE estimates across age groups and immunosuppression status. These findings support the use of test-negative controls and increase confidence in COVID-19 VE estimates produced by test-negative design studies.